Preparation and characterization of copper/copper-coated silicon carbide composites for electronic packaging / Azida Azmi - Azida, Azmi (2012)
Metal matrix composites (MMCs) have great potentials as packaging materials among other composite groups because the properties can be engineered to the design needs. Copper matrix reinforced with silicon carbide particles has greater potential due to the fact that it has higher thermal conductivity compared to the widely used aluminum. However, the bonding between the copper matrix and the SiC reinforcement must be improved since there is interface issues which affect the thermophysical properties of the CuSiC composites. Therefore, the SiC is coated with a thin copper film via electroless coating technique which is least expensive, simple and can provide homogenous copper deposits. The SiC is first need to be cleaned, etched, sensitized and activated to prepare the SiC particles surface for copper to be deposited onto it. Then, an electroless copper coating bath is prepared and the SiC is coated under suitable temperature and pH to obtain a good coating on SiC particles. Then, the CuSiC composites are fabricated via powder metallurgy methodology by ball milling to mix the copper matrix and SiC reinforcement. Then the mixture is pressed under uniaxial compaction loading and sintered at 925oC for 2 hours. Then the samples are ready for characterization and testing. The SEM images showed the difference between the raw SiC and cleaned SiC after ultrasonically cleaned in solvent. After sensitizing and activation process, the SEM image showed that it has the catalytic elements during the activation process. Then, the SEM image after coating process showed the copper deposits on the SiC particles surface. The particle size distribution has increased from 45.639mm before cleaning to 45.993mm after cleaning. Then the size increased to 46.750mm after sensitizing and activation process. Then, the size increased to 48.100mm after coating process.